2000
DOI: 10.2519/jospt.2000.30.7.390
|View full text |Cite
|
Sign up to set email alerts
|

Electrothermally-Assisted Capsulorrhaphy (ETAC): A New Surgical Method for Glenohumeral Instability and Its Rehabilitation considerations

Abstract: Knowledge of current surgical procedures and the effect they have on healing tissue is important when developing rehabilitation guidelines. Recently, clinicians have been asked to treat patients who have undergone Electrothemally-Assisted Capsulorrhaphy (ETAC) for shoulder instability. The ultimate tensile strength of the tightened capsule is unknown during various timeframes following surgery. The use of thermal energy to shrink the shoulder joint capsule initially causes weakness of the collagen ultrastructu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…vent overstretching of tightened capsular tissues, particularly after thermal shrinkage procedures that induce an initial decrease in collagen tensile strength. 95,98 We restrict axial loading of the upper extremity for 6 weeks. For cases with an anterior component of instability, we restrict external rotation range of motion to 30°(0°abduction) for the first 4 postoperative weeks and avoid combined external rotation and abduction range of motion for the first 6 postoperative weeks.…”
Section: Anterior Stabilizationmentioning
confidence: 99%
“…vent overstretching of tightened capsular tissues, particularly after thermal shrinkage procedures that induce an initial decrease in collagen tensile strength. 95,98 We restrict axial loading of the upper extremity for 6 weeks. For cases with an anterior component of instability, we restrict external rotation range of motion to 30°(0°abduction) for the first 4 postoperative weeks and avoid combined external rotation and abduction range of motion for the first 6 postoperative weeks.…”
Section: Anterior Stabilizationmentioning
confidence: 99%
“…Some clinicians have reported that it is easier to control the temperature (maintain a constant temperature) using the radiofrequency versus the laser method. 29,39,56 …”
Section: Figurementioning
confidence: 99%
“…Some clinicians have advocated immobilization during the first 2 to 4 weeks while others have suggested gentle restricted motion. 13,56 Most rehabilitation programs have been based on anecdotal clinical observations and preliminary data. In this section, we begin by discussing previously published rehabilitative programs.…”
Section: Rehabilitation Following Thermal-assisted Capsular Shrinkagementioning
confidence: 99%
See 2 more Smart Citations